2018
DOI: 10.1177/1591019918792231
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical clipping and endovascular treatment of middle cerebral artery aneurysms in an interdisciplinary treatment concept: Comparison of long-term results

Abstract: Objective Treatment of middle cerebral artery (MCA) aneurysms has been historically considered as the almost exclusive domain of microsurgical clipping. This retrospective single-center study assesses whether microsurgical clipping or endovascular treatment (i.e. coiling and/or stenting) for MCA aneurysms yielded better occlusion rates and clinical outcome. Methods We identified patients with a minimum cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 23 publications
1
18
1
Order By: Relevance
“…Particularly with regard to the Web group, we observed a clear learning curve, so our data may underestimate the potential of the WEB device in this challenging subgroup of aneurysms. Otherwise in contrast to other studies, 3 we have a very limited selection bias for endovascular treatment. This shows that a wide variety of complex MCA bifurcation aneurysms can be treated using endovascular means alone.…”
Section: Limitationsmentioning
confidence: 73%
See 1 more Smart Citation
“…Particularly with regard to the Web group, we observed a clear learning curve, so our data may underestimate the potential of the WEB device in this challenging subgroup of aneurysms. Otherwise in contrast to other studies, 3 we have a very limited selection bias for endovascular treatment. This shows that a wide variety of complex MCA bifurcation aneurysms can be treated using endovascular means alone.…”
Section: Limitationsmentioning
confidence: 73%
“…Recent publications demonstrate good clinical outcomes and low complication rates for both methods. 3,4 An essential point is that when we compared the 2 methods, the investigation objective is the same. Therefore, we present our endovascular treatment data of MCA bifurcation aneurysms from 2 hospitals (Klinikum Augsburg and Schoen Klinik, Vogtareuth, Germany).…”
mentioning
confidence: 99%
“…As per a paper published by David et al in 1999, occlusion rates were around 90% [ 29 ]. A more recently published retrospective study involving 92 patients with MCA aneurysms, of which 54 underwent clipping, found the post-clipping occlusion rate to be 96.3% [ 30 ]. A meta-analysis published by Toccaceli et al concluded that the long-term complete occlusion rate after surgery is 95%, thus strengthening the previous studies’ findings [ 31 ].…”
Section: Reviewmentioning
confidence: 99%
“…Treatment of exposed steel plates after surgery for fractures of foot and ankle is complicated, and presently, microsurgical repair treatment is a particularly advanced method used to clean the wound (4). Microsurgery is a subject of fine operations on fine tissues using optical magnification.…”
Section: Introductionmentioning
confidence: 99%